Green synthesis of Colocasia esculenta-based silver nanoparticles: characterization and transdermal delivery for anti-inflammatory applications - Wang, Xiaobo; Wang, Wanjuan; Ejaz, Areeba; Mehmood, Maira; Ahmad, Nadeem; Nazir, Imran; Shahzad, Yasser; Bai, Tianshuo (Frontiers in Pharmacology, 2025)
The current study aims to develop chitosan transdermal patches containing AgNPs synthesized and characterized from C. esculenta to reduce inflammation. Silver nanoparticles (AgNPs) were prepared utilizing the C. esculenta extract and characterized through Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), zeta potential measurements, and particle size analysis. The AgNPs were incorporated into chitosan-based transdermal patches, which were assessed for physicochemical properties, dermal compatibility, and anti-inflammatory effectiveness. In vitro protein denaturation and in vivo carrageenan-induced paw edema models evaluated anti-inflammatory efficacy. Characterization verified that the AgNPs were stable and spherical. The transdermal patches were biocompatible, had uniform thickness, and were extremely adhesive. The anti-inflammatory effects of AgNP-loaded patches were found to be superior to those of diclofenac sodium in in vivo studies, while in vitro studies revealed a notable inhibition of protein denaturation (p < 0.05). The current study offers new evidence that transdermal drug delivery systems derived from C. esculenta can effectively and sustainably manage inflammation.